Teaching Academic Writing in an EAP Course: Lecturers’ Perceptions of the EGAP and ESAP Approaches - Mohd Basari, Shahrul Nizam (ZES Rokman Resources, 2022)
The field of English for Academic Purposes (EAP) has seen English for General Academic Purposes or EGAP as a popular approach adopted by many practitioners (Basturkmen, 2006). It has been regarded as a model that helps EAP practitioners in their course, particularly in managing their students and preparing the course materials. In this model, EAP courses are not designed to cater to one specific discipline but are built around a general approach that is concerned with a common core of universal skills or language forms which can cater to various disciplines in an institution (Hyland & Hamp-Lyons, 2002). However, some claim that EAP is not about improving generic language abilities but it should be helping students to develop communicative skills in specific academic and professional settings. They highlighted the notion of specificity as a key issue in EAP (Hyland, 2006) and have argued for the use of English for Specific Academic Purposes (ESAP) as a better approach than EGAP. This argument has led this study to investigate the perceptions of lecturers who teach an EAP course that adopts the EGAP model in teaching academic writing. Fifteen lecturers from a language centre in a Malaysian public university were selected using the purposive sampling. The aim was to find out their views of the EGAP approach as well as ESAP. Interviews were done and the data were qualitatively analysed using the thematic analysis. Initial findings revealed their limited knowledge of EGAP and ESAP. There were also mixed responses regarding the effectiveness between the two approaches. Finally, it is proposed that the EAP course should integrate both EGAP and ESAP approaches to improve the academic writing course.